Towards A Personal Data Protection Regime In Malaysia - Khaw, Lake Tee (Journal of Malaysian and Comparative Law, 2002)
Data protection is a relatively new legal concept. Within the context of privacy, it is often referred to as ’information privacy’, that is, the interest of the person in controlling the information held by others about him. The first data protection law is said to have been enacted in the German state of Hesse in 1970 although Sweden was probably the first country to enact a national data protection law in 1973. International initiatives on rules and guidelines governing data protection soon followed suit and in the 1980s, the Organisation for Economic Cooperation and Development (OECD) released its Guidelines Governing the Protection of Transborder Data Flows of Personal Data, and the Council of Europe, the Convention for the Protection of Individuals with regard to the Automatic Processing of Personal Data. These two initiatives are considered the precursors of current data protection laws, and together with the EU Data Protection Directive (95/46/EC), provide useful basic principles for data protection.